Effects of Tiffin Practices on the Health of School Students in Makawanpur District, Nepal - Adhikari, Ram Prasad; Adhikari, Bhashkar Chandra; Dhimal, Ashmita; Khadka, Krishna Lila; Shrestha, Shriya; Pudasaini, Sushma; Neupane, Sushma (International Research Journal of MMC, 2023)
The main goals of the study are to explore the existing tiffin practices among school students, and assess the effects of tiffin practices on their health. The study was conducted in 2023, among 100 students of four schools out of 65 community schools in Hetauda sub-metropolitan in Makawanpur district. Second stage cluster sampling method was adopted to select the study area and the students were selected with simple random sampling method from different grades (1-12) of the community schools of Hetauda sub-metropolitan. Semi-structured questionnaire and checklist were used to collect the data and information. Among them 66.00 % school students consumed packed food where only 21.00% of the students consumed homemade food as tiffin. Among the surveyed 64 students, 59.4% of students had faced stomachache, 29.7% students had faced vomiting, 4.7% encountered nausea and 6.3% underwent allergies. Chi-square test was employed to test the null hypothesis. Age, gender and grade were significantly associated with tiffin practices (p≤ .05). There was no significant association between packed food and health hazards (p= .347). Lack of time of the parents, imitation of the peers, taste of junk food, lack of awareness led the consumption of junk or packed food that caused various health hazards on school going children.